Chili piquin (Capsicum annuum var. Aviculare) established on a plastic coating and space arrangement - Megchún-García, Juan Valente; Rebolledo-Martínez, Andrés; del Angel-Pérez, Ana Lid; Nataren-Vel´´azquez, Jeremías; Capetillo-Burela, ´Ángel (Ecosistemas y Recursos Agropecuarios, 2024)
The piquín chile intercropped in fruit trees has shown to be profitable for some agroecosystems in Mexico. Due to the importance of this vegetable, in the Cotaxtla Experimental Field of INIFAP, under rainfed conditions, an experiment was carried out to evaluate the growth and production of piquín chili, with three planting densities in bare soil and with plastic cover. The experimental design used was randomized blocks in divided plots. The variables evaluated were: plant height, stem thickness, floral buds, flowers, fruits and yield. The results showed that the use of plastic cover in chile piquín was statistically better than the treatment with bare soil in the variables plant height, stem diameter, number of shoots, flowers and fruits, with a yield of 7.53 t ha-1 that equivalent to 108% higher than the treatment with bare soil. The planting density of 25 000 plants per hectare was statistically higher than the other densities evaluated. The best density was 2 500 plants ha with plastic cover with a yield of 7.53 t ha-1.